Innovative models of healthcare delivery: an umbrella review of reviews. Issue 2 (23rd February 2023) - Roberts, Natalie; Carrigan, Ann; Clay-Williams, Robyn; Hibbert, Peter D; Mahmoud, Zeyad; Pomare, Chiara; Fajardo Pulido, Diana; Meulenbroeks, Isabelle; Knaggs, Gilbert Thomas; Austin, Elizabeth E; Churruca, Kate; Ellis, Louise A; et al.
Abstract : Objective: To undertake a synthesis of evidence-based research for seven innovative models of care to inform the development of new hospitals. Design: Umbrella review. Setting: Interventions delivered inside and outside of acute care settings. Participants: Children and adults with one or more identified acute or chronic health conditions. Data sources: PsycINFO, Ovid MEDLINE and CINAHL. Primary and secondary outcome measures: Clinical indicators and mortality, healthcare utilisation, quality of life, self-management and self-care and patient knowledge. Results: A total of 66 reviews were included, synthesising evidence from 1272 primary studies across the 7 models of care. Virtual care was the most common model studied, addressed by 47 (73%) of the reviews. Common outcomes evaluated across reviews were clinical indicators and mortality, healthcare utilisation, self-care and self-management, patient knowledge, quality of life and cost-effectiveness. The findings indicate that the innovative models of healthcare we identified in this review may be effective in managing patients with a range of acute and chronic conditions. Most of the included reviews reported evidence of comparable or improved care. Conclusions: A consideration of local infrastructure and individual patient characteristics, such as health literacy, may be critical in determining the suitability of models of care for patients and their implementation in local health systems. Trial registration number: 10.17605/OSF.IO/PS6ZU.